Imagining Manila literature, empire and orientalism - Sykes, Tom (London I.B. Tauris, 2021)
"The city of Manila is uniquely significant to Philippine, Southeast Asian and world history. It played a key role in the rise of Western colonial mercantilism in Asia, the extinction of the Spanish Empire and the ascendancy of the USA to global imperial hegemony, amongst other events. This book examines British and American writing on the city, situating these representations within scholarship on empire, orientalism and US, Asian and European political history. Through analysis of novels, memoirs, travelogues and journalism written about Manila by Westerners since the early eighteenth century, Tom Sykes builds a picture of Western attitudes towards the city and the wider Philippines, and the mechanics by which these came to dominate the discourse. This study uncovers to what extent Western literary tropes and representational models have informed understandings of the Philippines, in the West and elsewhere, and the types of counter-narrative which have emerged in the Philippines in response to them."-- Provided by publisher
"First published in Great Britain in 2021"--Title page verso.
Keywords: Orientalism; Literature; Orientalism in literature; Manila (Philippines) -- History